Numerical analysis of in-cylinder flow - Afiq, Hamdan (2008)
This thesis deals with numerical analysis of in-cylinder by using computer aided engineering software. The objective of this thesis is simulating the flow inside the combustion chamber using the computational fluid dynamics. The thesis describes the pattern of flow that effect from several of the valve lifts. The models of the combustion were analyzed and distinguished using the pattern or topology of flow in the combustion chamber. From the results, it is observed that analysis using a computational fluid dynamics can predict and simulate the pattern of flow in the combustion chamber. The size of meshing can affect the results. The size of meshing play big role to produce an accuracies data.